104k views
0 votes
Y = x – 6 x = –4 what is the solution to the system of equations? (–8, –4) (–4, –8) (–4, 4) (4, –4

User ZenBalance
by
5.4k points

2 Answers

2 votes

Answer:

(- 4, - 10 )

Explanation:

Given the 2 equations

y = x - 6 → (1)

x = - 4 → (2)

Substitute x = - 4 into (1) for corresponding value of y

y = - 4 - 6 = - 10

Solution is (- 4, - 10 )

User Kelgwiin
by
5.9k points
4 votes

Answer:

the answer is b (-4,-8)

Explanation:

i got it right top one is wrong

User Abkrim
by
5.2k points